2021
DOI: 10.1088/1361-6463/abe6cf
|View full text |Cite
|
Sign up to set email alerts
|

A correlation of lattice distortion with the magnetic properties of calcium doped bismuth ferrite thin films

Abstract: In this work, Bi1−x Ca x FeO3 (for x = 0.00–0.30) single-phase thin films were developed on clean glass substrates via simple spray pyrolysis technique. The microscopic crystal structure and magnetic characteristics of the Ca modified thin films were investigated. X-ray diffraction study confirms the hexagonal structure with the space group R3c for all the prepared thin film samples. The crystallite sizes and lattice strains were computed by using the Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…For example, Raman spectroscopy is used to analyze the structural changes of substances aer doping elements. [8][9][10] Furthermore, Raman spectroscopy is also used in medical systems to detect cancer, diseases related to the human nervous system and other diseases. [11][12][13][14][15] However, in situ Raman spectroscopy can more accurately characterize the transformation law of the structural characteristics of the objects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Raman spectroscopy is used to analyze the structural changes of substances aer doping elements. [8][9][10] Furthermore, Raman spectroscopy is also used in medical systems to detect cancer, diseases related to the human nervous system and other diseases. [11][12][13][14][15] However, in situ Raman spectroscopy can more accurately characterize the transformation law of the structural characteristics of the objects.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of bulk BFO in functional applications is consequently restricted by these issues. Recently, many researchers have shown that rare-earth elements , or alkaline-earth elements , doping at the A site, as well as partial replacement of B site ions by metal elements from the transition group, , are effective ways to unlock the spiral structure and enhance the magnetic characteristics of BFO. According to the previous reports, the magnetism and ferroelectricity of BFO were increased when Bi and Fe were partially substituted at the same time by ions like Er and Nb, Sr and Mn, Dy and Mn, etc.…”
Section: Introductionmentioning
confidence: 99%